IOT – ChargeItSpot - S, Murthy S; S, Deepika K; Kumar, G Sai Dheeraj; M, Ashwini; H, Vinutha (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
The objective of this project is inserting the coin using charge for your mobile phone in public places. This project is very useful to people who are all using mobile phone without charging condition in public places. In this project, who are all using mobile phones in outside of home are office without charging condition. The IOT coin based mobile phone charger is very useful to that person for using coin to charge for that mobile. In this project we are implementing more application by using the same concept like water filling and emergency alert to nearby hospitals and police stations by using the IOT concept.